2018
DOI: 10.15282/jmes.12.3.2018.12.0343
|View full text |Cite
|
Sign up to set email alerts
|

Performance studies on cryogenic treated carbide cutting tool for turning of AISI304 steel

Abstract: This paper attempts to compare and contrast cryogenic treated and untreated carbide cutting tool in turning operation of AISI304 steel. Machining parameters, namely cutting speed, feed rate and depth of cut are optimized for cryogenic treated tools. Tool life of the insert was determined based on the tests performed such as hardness, surface roughness and maximum wear. A design of experiments (DOE) and an analysis of variance (ANOVA) have been incorporated in the study. The objective of the paper is to determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…In an cryogenic turning of AISI & MDN 250 steel, found a reduction in wear and improved surface finish, are other considerable findings which enhanced machinability [4,5]. Similarly, Varghese et al [6] in his inveatigation, also claimed significant reduction in tool wear in CT machining in contrat with non CT machining, respectively.…”
Section: Introductionmentioning
confidence: 90%
“…In an cryogenic turning of AISI & MDN 250 steel, found a reduction in wear and improved surface finish, are other considerable findings which enhanced machinability [4,5]. Similarly, Varghese et al [6] in his inveatigation, also claimed significant reduction in tool wear in CT machining in contrat with non CT machining, respectively.…”
Section: Introductionmentioning
confidence: 90%
“…Significance level of 0.05). This would lead to evaluating the relative influence of each machining parameter on the responses [16,17]. ANOVA results for arithmetic mean surface roughness (Ra) and cutting force (Fy) are illustrated in Table 4.…”
Section: Anova Analysismentioning
confidence: 99%
“…Nowadays, carbide tools with the diverse coatings are utilized as a option for PCBN and ceramics tools. The much of the time utilized coatings incorporate TiN, TiAlN, TiCN, TiAlCN Al2O3 [9][10][11][12][13]. The performance of cutting tool with and without coatings in terms of cutting force [3][4], surface roughness [9][10][11][12][13], chip morphology [15] and acoustic emission [16] with various grades of the cutting tools is studied by different researchers and in-depth review related process parameter is reported by Ambhore et al [17].…”
Section: Introductionmentioning
confidence: 99%